A Critical Review of the Effect of Dietary Fiber Intake on the Prevention of Colorectal Cancer in Eastern Asian Countries. (18th January 2021) - Yang, Yunfan; Yang, Li; Zhou, Liping; Tang, Siyuan
Abstract : Background . Colorectal cancer has become the second most common type of cancer in females and the third most common type of cancer in males. The incidence rate of colorectal cancer is increasing along with the change of lifestyle and dietary habits in East Asia. The cause of colorectal cancer is complex; environmental factors and genetic factors affect each other. Dietary fiber is considered as the prevention of colorectal cancer. Epidemiological data in Europe and America have suggested that dietary fiber intake is negatively correlated with colorectal cancer incidence rate. However, the evidence among different populations is inconsistent, and little is known about these associations in Eastern Asian areas. Objectives . To critically review all available human epidemiological data on the relationship between dietary fiber intake and colorectal cancer in Eastern Asian countries and make recommendations for these populations. Methodology . PubMed and Embase were used to search online research papers regarding the relationship between dietary fiber intake and the risk of colorectal cancer in Eastern Asian. We located 9 publications, of which the sample size ranged from 266 to 78, 326. Results . Five case-control studies, as well as one prospective study, have examined significant preventive effects of dietary fiber intake on the risk of colorectal cancer while evidence from three prospective cohorts suggested no preventive effects of dietary fiber intake on colorectal cancer among these populations. There is no consistent conclusion on the protective effect of dietary fiber from different sources and types. Conclusion . The association between dietary fiber intake and colorectal cancer risk in Chinese, Japanese, and Korean is considered to be plausible by the available literature. This current review cannot substantiate the preventive effect of dietary fiber intake on colorectal cancer due to the limited available evidence analyzed.